Pain Taxonomy - Classifying Needle Inflicted Pain Sensation - Jayavalan, Jenani (Universiti Teknologi Petronas, 2011)
Acupuncture is an interesting area in traditional healing. It has proven to be effective in healing many types of ailments. Namely pain related ailments like headache, flu and minor back pains. Acupuncture has also managed to heal certain cases that couldn't be healed by modern medicine like cancer and stroke in some patients. Ironically, many patients are greatly phobic of treatments that involve piercing of needles. Mainly because of the pain inflicted. So they tend to hinder taking the treatment even when they really need it. The motivation of this study is to help reduce phobia towards needle inflicted pain sensation using haptic technology. The study proposes a taxonomy to classify needle inflicted pain sensation in the haptic domain. The objectives are to eliminated vagueness of describing pain sensation. Also in further views, the study is seen to be futuristic as it is the stepping stone to research in the area of pain related phobia reduction in both haptic and virtual reality sector. Having established a taxonomy to classify needle inflicted pain sensation will help in being the baseline to build future systems in Virtual Reality and touch solutions to reduce pain related phobia. It will also greatly help the acupuncture field to gain client's confidence as vagueness of describing pain sensation will be eliminated. iii